2017
DOI: 10.1002/dta.2297
|View full text |Cite
|
Sign up to set email alerts
|

Roadside drug testing: An evaluation of the Alere DDS®2 mobile test system

Abstract: The number of drivers using drugs has increased over the last few years, and is likely to continue its upward trend. Testing drivers for alcohol use is routine and standardized, but the same is not true for the identification of driving under the influence of drugs (DUID). The Drug Evaluation and Classification Program (DECP) was developed to train police officers to recognize the signs and symptoms of recent drug use and remains an invaluable program; however, there are insufficient numbers of these highly tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Other studies established that screening devices must present higher standards (sensitivity ≥ 80%, specificity ≥ 90% and accuracy ≥ 95%), so that it can be considered a satisfactory test (Strano-Rossi et al, 2012). Based on this information, and the data collected in our review, it is possible to verify that only Dräger DrugTest 5000 ® (DDT5000) and Alere TM DDS ® 2 (DDS2) devices fits the recommendation for the investigation of cannabis metabolites in OF, presenting sensitivity and specificity greater than 80% in a considerable number of studies (Beirness, Smith, 2017;Gjerde et al, 2018;Newmeyer et al, 2017;Rohrig et al, 2018;Strano-Rossi et al, 2012;Swortwood et al, 2017). However, it is important to note that some studies have found low specificity for the DDT5000 device, even though they have found satisfactory sensitivity (Domingo-Salvany et al, 2017;Lema-Atán et al, 2019;Logan, Mohr, Talpins, 2014).…”
Section: Resultsmentioning
confidence: 71%
“…Other studies established that screening devices must present higher standards (sensitivity ≥ 80%, specificity ≥ 90% and accuracy ≥ 95%), so that it can be considered a satisfactory test (Strano-Rossi et al, 2012). Based on this information, and the data collected in our review, it is possible to verify that only Dräger DrugTest 5000 ® (DDT5000) and Alere TM DDS ® 2 (DDS2) devices fits the recommendation for the investigation of cannabis metabolites in OF, presenting sensitivity and specificity greater than 80% in a considerable number of studies (Beirness, Smith, 2017;Gjerde et al, 2018;Newmeyer et al, 2017;Rohrig et al, 2018;Strano-Rossi et al, 2012;Swortwood et al, 2017). However, it is important to note that some studies have found low specificity for the DDT5000 device, even though they have found satisfactory sensitivity (Domingo-Salvany et al, 2017;Lema-Atán et al, 2019;Logan, Mohr, Talpins, 2014).…”
Section: Resultsmentioning
confidence: 71%
“…By focusing on these issues, the Roadside Testing Assessment (ROSITA)-1 and ROSITA-2 and the Driving Under the Influence of Drugs, Alcohol and Medicines (DRUID) projects evaluated the performance parameters (sensitivity, specificity and accuracy) of several on-site drug tests in urine and, especially, in OF, with unsatisfactory results overall. [3][4][5] However, in the last few years, several publications have addressed the general evaluation of on-site drug tests in roadside traffic controls using OF as biological matrix [6][7][8][9] and the investigation of a correlation between OF and blood concentrations of centrally active substances. [10][11][12] Some of those studies concluded that OF is a suitable matrix for the detection of recent drug consumption.…”
Section: Introductionmentioning
confidence: 99%